2023
DOI: 10.1001/jamanetworkopen.2023.23405
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Adverse Reactions, Antibody Patterns, and 12-month Outcomes in the Mother-Infant Dyad After COVID-19 mRNA Vaccination in Pregnancy

Abstract: ImportanceLongitudinal data on COVID-19 messenger RNA (mRNA) vaccine reactogenicity and immunogenicity in pregnancy and for the mother-infant dyad are needed.ObjectiveTo examine COVID-19 mRNA vaccine reactogenicity and immunogenicity in pregnancy and observe longitudinal maternal and infant outcomes.Design, Setting, and ParticipantsThis prospective cohort study of pregnant individuals enrolled in the COVID-19 Vaccination in Pregnancy and Lactation study from December 1, 2020, through December 31, 2021, with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Previous studies have demonstrated that timing of initiation of COVID-19 vaccination in pregnancy influenced the levels of maternal vaccine-induced antibodies at delivery and transplacental transfer to the umbilical cord 14,16,24,33,34 . Knowledge is lacking, however, regarding how the timing of not only the first, but also the second dose of the mRNA vaccine in pregnancy, impacts maternal antibody levels and persistence of antibody in infants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that timing of initiation of COVID-19 vaccination in pregnancy influenced the levels of maternal vaccine-induced antibodies at delivery and transplacental transfer to the umbilical cord 14,16,24,33,34 . Knowledge is lacking, however, regarding how the timing of not only the first, but also the second dose of the mRNA vaccine in pregnancy, impacts maternal antibody levels and persistence of antibody in infants.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal vaccination against COVID-19 has been shown to effectively reduce COVID-19 related hospitalization rates in infants younger than 6 months 9,10 , through the transplacental transfer of maternal COVID-19 vaccine induced antibodies 16,17 . Here, using systems serology, we profiled maternal antibodies in 100 infants up to 12 months of age in unprecedented detail.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies examining COVID-19 vaccination during pregnancy have demonstrated the transplacental antibody transfer of anti-spike immunoglobin (Ig) G antibodies. 12 , 13 , 14 , 15 , 16 While there are limited data on the persistence of maternal anti-spike IgG antibodies in infants, 16 , 17 no study has performed comprehensive profiling of maternal COVID-19 vaccine-induced antibodies that persist in infants through 12 months of age, including all IgG subclasses, Fc-receptor (FcR) binding profiles, and against both SARS-CoV-2 wild-type and variants of concern (VOCs) including B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 (Delta), P.1 (Gamma), and B.1.1.529 (Omicron) variants. FcR binding is a critical consideration, as the Fc region of the antibodies plays an important role in protection against infection and the resolution of SARS-CoV-2 infection 18 , 19 by inducing the antiviral activity of the innate immune system.…”
Section: Introductionmentioning
confidence: 99%